Disability-adjusted life years (DALYs) for 291 diseases and injuries in 21 regions, 1990–2010: a systematic analysis for the Global Burden of Disease Study 2010 - Belinda Gabbe (The Lancet, 2012)
Background Measuring disease and injury burden in populations requires a composite metric that captures bothpremature mortality and the prevalence and severity of ill-health. The 1990 Global Burden of Disease study proposeddisability-adjusted life years (DALYs) to measure disease burden. No comprehensive update of disease burdenworldwide incorporating a systematic reassessment of disease and injury-specifi c epidemiology has been donesince the 1990 study. We aimed to calculate disease burden worldwide and for 21 regions for 1990, 2005, and2010 with methods to enable meaningful comparisons over time.Methods We calculated DALYs as the sum of years of life lost (YLLs) and years lived with disability (YLDs). DALYswere calculated for 291 causes, 20 age groups, both sexes, and for 187 countries, and aggregated to regional andglobal estimates of disease burden for three points in time with strictly comparable defi nitions and methods. YLLswere calculated from age-sex-country-time-specifi c estimates of mortality by cause, with death by standardised lost life expectancy at each age. YLDs were calculated as prevalence of 1160 disabling sequelae, by age, sex, and cause, andweighted by new disability weights for each health state. Neither YLLs nor YLDs were age-weighted or discounted.Uncertainty around cause-specifi c DALYs was calculated incorporating uncertainty in levels of all-cause mortality,cause-specifi c mortality, prevalence, and disability weights.Findings Global DALYs remained stable from 1990 (2·503 billion) to 2010 (2·490 billion). Crude DALYs per 1000 decreasedby 23% (472 per 1000 to 361 per 1000). An important shift has occurred in DALY composition with the contribution ofdeaths and disability among children (younger than 5 years of age) declining from 41% of global DALYs in 1990 to 25%in 2010. YLLs typically account for about half of disease burden in more developed regions (high-income Asia Pacifi c,western Europe, high-income North America, and Australasia), rising to over 80% of DALYs in sub-Saharan Africa. In1990, 47% of DALYs worldwide were from communicable, maternal, neonatal, and nutritional disorders, 43% fromnon-communicable diseases, and 10% from injuries. By 2010, this had shifted to 35%, 54%, and 11%, respectively.Ischaemic heart disease was the leading cause of DALYs worldwide in 2010 (up from fourth rank in 1990, increasing by29%), followed by lower respiratory infections (top rank in 1990; 44% decline in DALYs), stroke (fi fth in 1990; 19%increase), diarrhoeal diseases (second in 1990; 51% decrease), and HIV/AIDS (33rd in 1990; 351% increase). Majordepressive disorder increased from 15th to 11th rank (37% increase) and road injury from 12th to 10th rank (34%increase). Substantial heterogeneity exists in rankings of leading causes of disease burden among regions.Interpretation Global disease burden has continued to shift away from communicable to non-communicable diseasesand from premature death to years lived with disability. In sub-Saharan Africa, however, many communicable,maternal, neonatal, and nutritional disorders remain the dominant causes of disease burden. The rising burden frommental and behavioural disorders, musculoskeletal disorders, and diabetes will impose new challenges on healthsystems. Regional heterogeneity highlights the importance of understanding local burden of disease and setting goalsand targets for the post-2015 agenda taking such patterns into account. Because of improved defi nitions, methods,and data, these results for 1990 and 2010 supersede all previously published Global Burden of Disease results.